Internal factor analysis of cleanliness, health, safety, and environment sustainability implementation in food and beverage services - Ridho, Sari Lestari Zainal; Sabli, Habsah Binti Haji Mohamad; Ibrahim, Kartini Binti Che; Detmuliati, Alditia; Alfitriani, Alfitriani; Jauhari, Hadi (Journal of Business on Hospitality and Tourism, 2022)
The Covid-19 pandemic has triggered the journey of life with a new order, in order to adapt to the situation in dealing with disruptions caused by the pandemic. The government, through the Ministry of Tourism and Creative Economy, implements standards and guidelines for the protocol for Hygiene, Health, Safety, and Environmental Sustainability in the tourism sector. Of course this must be applied to all business actors in the tourism industry, including service and beverage providers, which is one of it is bakery. As a tourism owner or entrepreneur and employer, it is important to participate in implementing the CHSE protocol in the business environment. For this purpose, it is important to evaluate the application of the CHSE. In order to achieve that purpose, it is necessary to conduct a research by analyzing the internal factors, the strengths and weaknesses, in the implementation of CHSE, as the objective of this research. This research is a pilot research project. The sample of this research is a brand of bakery business with some branches in the city of Palembang. Data collection was carried out using a questionnaire distributed to employees and employers during the fourth quarter of 2021. The results of this study indicate that in the bakery business it can be said that in the implementation of CHSE, the business has more strength factors compared to the weakness factor, which means that the CHSE implementation activities that have been carried out are good, by employees and employers.